2007
DOI: 10.1007/s10832-007-9058-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric interactions in ferromagnetic-piezoelectric layered structures: Phenomena and devices

Abstract: Layered magnetostrictive-piezoelectric structures are multifunctional due to their dual-responsiveness to mechanical and electromagnetic forces. Here, we discuss studies of magnetoelectric (ME) interactions in ferrite-lead zirconate titanate (PZT) and terfenol-PZT material couples. Key findings include: (1) the observation of a giant lowfrequency ME effect in the layered systems; (2) data analysis based on our model for low frequency ME effects;(3) observation and theory of enhanced ME coupling at the electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 20 publications
0
38
0
2
Order By: Relevance
“…1,2 Microwave frequency response is important for a number of device applications and has been explored within the context of exchange bias. [3][4][5][6][7] The exchange bias of FM layers within a composite FM/AFM multilayer can be controlled by the FM layer thickness. Tailoring these thicknesses within a multilayer can give rise to a range in the absorption frequencies and has applications in broadband microwave shielding.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Microwave frequency response is important for a number of device applications and has been explored within the context of exchange bias. [3][4][5][6][7] The exchange bias of FM layers within a composite FM/AFM multilayer can be controlled by the FM layer thickness. Tailoring these thicknesses within a multilayer can give rise to a range in the absorption frequencies and has applications in broadband microwave shielding.…”
Section: Introductionmentioning
confidence: 99%
“…where K 1 is the fourth-order crystalline cubic anisotropy with α i being the direction cosines of M in the cubic axes, K ┴ is a second-order anisotropy term normal to the film, and the second-order K u anisotropy term is included to represent the inequivalence between [110] and [1][2][3][4][5][6][7][8][9][10]. Here, it is assumed that the K u axis aligns along [110].…”
Section: A Fmr Of Heusler Filmsmentioning
confidence: 99%
“…The perpendicular and in-plane cubic and perpendicular uniaxial anisotropy terms are usually considered to be due to the strain in the crystal lattice caused by the lattice constant mismatch between the Co 2 MnSb film and the substrate on which it was grown. 25 The in-plane uniaxial term is due to the fact that there is a difference between the [110] and [1][2][3][4][5][6][7][8][9][10] crystallographic directions despite the high symmetry zinc-blende structure of the material. 26 Heinrich et al, 27 , 28 have recently found an alternative mechanism of in-plane or perpendicular magnetic anisotropy in Heusler alloys related to ordered lattice defects which are more pronounced in thick films, such as epitaxially grown NiMnSb(001) films grown on an InGaAs/InP(001) template.…”
Section: A Fmr Of Heusler Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this assumption simplifies the problem greatly, it inevitably makes the GLSM deviate from reality to some extent. As is known, practical composites formed by alternate piezoelectric and piezomagnetic layers generally have three kinds of inter-couplings among the mechanical, electric and magnetic fields simultaneously [20][21][22][23]. Therefore, it is easy to expect that the mechanical, electric and magnetic interfacial imperfections may also have similar inter-couplings.…”
Section: Introductionmentioning
confidence: 99%